Comparison of the effect of Propofol, Etomidate and Thiopental on Seizure duration following electro convulsion therapy:A clinical trial study - Ramin Amini; Sadeghali Taziki; Gholamreza Roshandel; Kazem Kazemnejad (مجله دانشگاه علوم پزشکی گرگان, 2019)
Background and Objective: Electro convulsion therapy (ECT) is one of the most common ways for treatment of psychiatric disorders. The aim of this study was to compare the effect of Propofol, Etomidate, and Thiopental on seizure and recovery duration following ECT. Methods: In this clinical trial study, 90 patients diagnosed with a psychiatric disorder by a psychiatrist, who need to be treated by ECT in 5 Azar hospital, Gorgan, north Iran. The patients were randomly divided into the three groups by simple random allocation method. Interventions included standard monitoring and pre-oxygenation with 100% FiO2 for 3 minutes for all patients in three groups. Anesthesia of the patients in the first, second, and third group was done with Thiopental (1.5 mg/kg), Propofol (0.6 mg/kg), and Etomidate (0.1 mg/kg), respectively. Administration of Succinyl Colin (0.5 mg/kg) as muscle relaxant and Atropine for prevention of bradycardia was uesd in all patients. Duration of seizure and recovery; changes in hemodynamic status including heart rate (HR) and mean arterial pressure (MAP); and amount of charge for ECT were recorded for each subject. Results: Mean of seizure duration in Thiopental, Propofol, and Etomidate groups were 43.72±11.81, 35.74±10.58 and 45.81±17.26 seconds, respectively (P<0.05). Amount of charge for ECT in 3 sessions of treatment and changes of HR were not different between the 3 groups. Changes of MAP in the Propofol group was significantly less than other two groups (P<0.05). Recovery time following ECT was the least in Etomidate group in comparison with Thiopental and Propofol (P<0.05). Conclusion: Ethomidate and Thiopental had the same effect on increasing seizure duration. However, due to the significant reduction in recovery time compared with Thiopental, Ethomidate may be considered as the best choice.